GONYAULACYSTA PARORTHOCERAS: A New Species of DINOFLAGELLATE CYST - Davey, Roger J. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1968)
Davey (1968 in press) emends the species Gonyaulacysta orthoceras Eisenack and also transfers it to the genus Cribroperidinium Neale and Sarjeant. By emending Eisenack's species the specimens described by Sarjeant (1966) as G. orthoceras, from the Lower Cretaceous of England, must now be excluded from this species. Hence, a new species is here erected to accommodate them.